2023
DOI: 10.1111/joor.13590
|View full text |Cite
|
Sign up to set email alerts
|

Adverse effect of botulinum toxin‐A injections on mandibular bone: A systematic review and meta‐analysis

Mahmoud S. Moussa,
Dona Bachour,
Svetlana V. Komarova

Abstract: IntroductionBotulinum toxin‐A (BTX) is a potent neurotoxin that is emerging in the scope of dental practice for its ability to temporarily paralyse musculature and reduce hyperfunction. This may be desirable in diseases/disorders associated with hyperactive muscles such as the muscles of mastication, most implicated in painful temporomandibular disorders (TMDs). The use of BTX extends beyond its indications with off‐label use in TMD's and other conditions, while potential adverse effects remain understudied. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 52 publications
0
9
0
Order By: Relevance
“…As a way of complementing the evidence on effectiveness, it is up to dental surgeons to evaluate the application of TxBA for bruxism, as new evidence, such as that of Balanta-Melo et al, (2019) and Moussa et al, (2023), despite being fragile and initial, indicates that the substance is capable of leading to bone resorption in the head of the jaw.…”
Section: Discussionmentioning
confidence: 99%
“…As a way of complementing the evidence on effectiveness, it is up to dental surgeons to evaluate the application of TxBA for bruxism, as new evidence, such as that of Balanta-Melo et al, (2019) and Moussa et al, (2023), despite being fragile and initial, indicates that the substance is capable of leading to bone resorption in the head of the jaw.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a meta-analysis from a systematic review suggested that bone loss has been mainly evaluated in the mandibular condyle in animal studies. In contrast, human studies are focused on the mandibular ramus (where the masseter muscle is inserted) [41]. However, due to a low number of human studies and small size samples, combined with short-term follow-ups and the lack of dose standardization, there is a need for more clinical research to determine if these bone changes may negatively impact structures such as the temporomandibular joint, which is vital for physiological processes [40,41].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, human studies are focused on the mandibular ramus (where the masseter muscle is inserted) [41]. However, due to a low number of human studies and small size samples, combined with short-term follow-ups and the lack of dose standardization, there is a need for more clinical research to determine if these bone changes may negatively impact structures such as the temporomandibular joint, which is vital for physiological processes [40,41]. A clinical study demonstrated that using the BoNTA intervention to manage myofascial pain in adult women resulted in thickness reduction of the injected muscles (both masseter and temporalis), and reduced bone volume in the mandibular condyle in a dose-dependent manner; nonetheless, non-injected muscles were not assessed [42].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the replacement of type IIa muscle fibers (anti-fatigue) for type IIb muscle fibers (non-anti-fatigue) and the replacement of contractile tissue with fat have also been observed in animal studies 14 16 . In addition, animal literature has found that these muscular alterations could worsen if we consider repeated injections of the treatment in masticatory muscles and as consequence lead to changes in mandibular bone which have been also demonstrated in clinical trials 18 20 .…”
Section: Introductionmentioning
confidence: 87%